2014
DOI: 10.1186/s12955-014-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing self-management in patients with diabetes mellitus type 2 in Germany: validation of a German version of the Summary of Diabetes Self-Care Activities measure (SDSCA-G)

Abstract: BackgroundOne of the most widely used self-reporting tools assessing diabetes self-management in English is the Summary of Diabetes Self-Care Activities (SDSCA) measure. To date there is no psychometric validated instrument in German to assess self-management in patients with diabetes mellitus. Therefore, this study aimed to translate the SDSCA into German and examine its psychometric properties.MethodsThe English version of the SDSCA was translated into German following the guidelines for cultural adaptation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
3
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 32 publications
10
69
3
7
Order By: Relevance
“…We found that health literacy is directly linked to the self-care behavior of foot care, which is consistent with the findings of Her- criterion of 0.70; this lack of reliability has also been a problem in other studies (Kamradt et al, 2014;Lee et al, 2016). , which should be addressed in a future study.…”
Section: Main Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…We found that health literacy is directly linked to the self-care behavior of foot care, which is consistent with the findings of Her- criterion of 0.70; this lack of reliability has also been a problem in other studies (Kamradt et al, 2014;Lee et al, 2016). , which should be addressed in a future study.…”
Section: Main Findingssupporting
confidence: 90%
“…(), while the linkage in this study was not mediated by empowerment. However, these findings should be interpreted with caution due to Cronbach's alpha of the foot‐care subscale of the SDSCA used in this study being below the usual criterion of 0.70; this lack of reliability has also been a problem in other studies (Kamradt et al., ; Lee et al., ). The subscale of foot care comprises only two items and such a small number of items in a subscale may result in a low Cronbach's alpha.…”
Section: Discussionmentioning
confidence: 63%
“…General diet and blood glucose testing presented interitem correlation over 0.9 whereas exercise correlation was moderate and foot care and medication adherence correlation were average. All these results are in agreement with the English version of SDSCA, with the Arabic version of SDSCA and with the German version of SDSCA [7][8][9].…”
Section: Introductionsupporting
confidence: 86%
“…Self-care and self-care ability have been explored in many studies (Cheng, Meng, Yang, & Zhang, 2013;Evers, Isenberg, Philipsen, Senten, & Brouns, 1993;Kamradt et al, 2014;Khankeh, Rahgozar, & Ranjbar, 2011;van Achterberg et al, 1991), especially since the "Self-care deficit of nursing" theory was proposed by Orem in the 1970s (Orem, 2001). Self-care deficit is the core of Orem's self-care theory and commonly linked with the nursing process.…”
mentioning
confidence: 99%